Media theory for A level the essential revision guide - Dixon, Mark (Routledge, 2020)
"Media Theory for A Level provides a comprehensive introduction to the 19 academic theories required for A Level Media study. From Roland Barthes to Clay Shirky, from structuralism to civilisationism, this revision book explains the core academic concepts students need to master to succeed in their exams."